The Importance of Forest Conservation: How Forests Affect Climate and Our Lives in Science Education in Primary Schools - Hidayani, Nurul (Jurnal Pendidikan, Kesehatan dan Olahraga, 2024)
Indonesia is a part of the world that has natural wealth and biodiversity that is very important for life, one of which is the forest. Indonesia's forests play an important role in maintaining the stability of the world's climate. The sustainability of the forest is the result of various processes that occur in the life of the forest ecology. A forest ecosystem has a social system consisting of humans, and then there is the ecosystem environment itself. Problems that occur, such as slashing and burning, are one of the factors that can have a significant impact on the existence of the environment and life in it. This article discussed forest sustainability and fostering a sense of environmental love for students in Indonesia by discussing various materials related to 1) The condition of forest sustainability in Indonesia. 2) Maintaining and promoting a sense of environmental love. The type of data used by the author in this research is data obtained from literature studies. In the process of writing this article, the author collects all data related to the topic of discussion, namely about the attitudes and behaviour of a person to preserve the forest and instill an attitude of environmental love. The aim of this article is to promote the values of forest conservation and love for the environment, especially at the level of primary education